The relationship between organizational culture and job satisfaction in Tenaga Nasional Berhad (TNB) Kuantan, Pahang / Mohamad Shah Razin Md Asri - Md Asri, Mohamad Shah Razin (2020)
This study examines the relationship between Organizational Culture and Job Satisfaction in Tenaga Nasional Berhad (TNB) Kuantan, Pahang. It also determines the Organizational Culture as independent variable which consists into four types, clan culture, adaptability culture, achievement culture and bureaucratic culture. Job Satisfaction was determined as dependent variable. A total of 33 questionnaires were distributed to the management staffs of TNB Kuantan, Pahang. The questionnaire was divided into 3 sections, which are section A to section C. Section A is a socio-demographic that consist five questions. Second, the organizational culture was in section B covered with clan culture, adaptability culture, achievement culture and bureaucratic culture. For the last section is section C, the questions cover on Job Satisfaction. The researcher conducted the study at TNB Kuantan, Pahang. Questionnaires are distributed to the management staffs of TNB in order to collect the data for the finding. The researcher interprets the data collected using Statiscal Package for the Social Science (SPSS). The objective of this study is to identify the relationship between types of organization culture on job satisfaction among management staffs in Tenaga Nasional Berhad (TNB), Kuantan Pahang and to identify the types of organization culture that mostly adopted among management staffs at Tenaga Nasional Berhad, Kuantan Pahang. The result obtained was documented in depth through this report. The researcher also comes up with several recommendation and suggestion for the future study.